165 Frail older patients have a greater improvement in physical quality of life following invasive management for non-ST elevation acute coronary syndrome. (May 2019) - Gu, Zhaotao Sophie; Chan, Danny; Beska, Ben; Sinclair, Hannah; Qiu, Weiliang; Kunadian, Vijay
Abstract : Introduction: Frailty, defined as a vulnerability to physiological stressors due to a decline in reserve with age, is common in older patients with non-ST elevation acute coronary syndrome (NSTEACS) and is associated with a disproportionately high morbidity and mortality. We aimed to determine how frailty influences physical quality of life (QoL) outcomes after invasive treatment for NSTEACS. Methods: 298 patients aged ≥75 years with NSTEACS were enrolled into a multicentre prospective observational study, 297 (99.7%) completed QoL questionnaires at baseline. Frailty was assessed using the Fried criteria, where a score of 0 is robust, 1 or 2 is pre-frail and ≥3 is frail. QoL was assessed by Short Form-36 (SF-36) questionnaire (license number QM033917) at baseline and 1 year follow-up. The norm-based physical component score (PCS), an aggregated summary score of the 8 SF-36 subscales, is reported. Results: Mean age was 80.4±4.8 years, 61.7% male, 86.6% received invasive treatment (percutaneous coronary intervention or coronary artery bypass grafting), and 234 (78.8%) patients completed 1-year follow-up QoL assessment. At presentation, 56 (18.9%) patients were robust, 160 (53.9%) were pre-frail and 81 (27.3%) were frail. There was no difference in proportional of patients received invasive management among frailty groups (89.3% of robust, 83.8% of pre-frail and 90.1% frail patients were treated invasively, p=0.30). Increasing frailty was associated with decreased physical QoL at both baseline and 1 year (p<0.001 for both time points). Although all frailty groups saw an increase in mean PCS, this difference was only statistically significant in pre-frail and frail patients (robust: 42.7±10.7 to 44.2±11.8, p=0.409; pre-frail: 37.7±11.1 to 41.3±11.4, p=0.001; frail: 27.9±8.5 to 32.5±12.6, p=0.04). In addition, only pre-frail and frail patients who received invasive treatment saw this significant improvement in PCS between baseline and 1 year, although numbers receiving medical therapy only was low (figure 1 ). Conclusion: Although frail older patients with NSTEACS have a poorer physical QoL overall, our data suggest frailty is associated with a greater improvement from baseline QoL in those who receive invasive treatment. Conflict of Interest: None